Cultural circles as a pedagogical possibility in the emancipation perspective: an experience in the proeja of a public school of Salvador - BA, Brazil - Vieira, Joana Lopes (2019)
This article is part of a doctoral research and aims to study the circle of culture inserted in the pedagogical praxis in the Program of Education of Young and Adults - PROEJA in a public school in Salvador, Bahia Brazil. We seek the conceptualization of Freire (1987) on cultural circles and Sousa Santos (2007) and Arroyo (2014) on the need to propose other pedagogies that recognize "other subjects" through a pedagogical experience. It is justified by the importance of cultural circles as a pedagogical proposal that extends the epistemological dimension by enabling the construction of new knowledge, consubstantiated by educational possibilities, different from hegemonic logic, based on dialogues, reflections and interactions. We conclude that cultural circles have enabled us to carry out the exercise of historical, political and cultural awareness, as well as to affirm their pertinence in the pedagogical practice for the education of young people and adults.